Rekonsiliasi Konjungtivitis Iritatif (IC) dan Penyakit Mata Kering (DED): Sebuah Tinjauan Literatur untuk Mengajukan Spektrum Penyakit Permukaan Okular Akibat Polusi - Maharani; Trijayanthi Utama, Winda; Virginia Irawati, Nur Ayu; Sutarto, Sutarto (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
The relationship between particulate matter (PM) and ocular surface disease (OSD) is contradictory. Occupational Health and Safety (OHS) literature in Indonesia consistently links high-dose PM10 (dust/smoke) exposure to Irritable Conjunctivitis (IC). Global epidemiological studies tend to focus on PM2.5 and NO2 as the primary causative agents of chronic DED, while ambient PM10 plays a less significant role. The aim of this study was to reconcile this conflicting evidence using a Systematic Literature Review (SLR) method. A total of 42 studies were narratively synthesized and categorized into three lines of evidence: Indonesian occupational exposure (OHS), global ambient exposure (epidemiology), and pathophysiological mechanisms (in vitro/in vivo). The results revealed a